Development Apllication for Medicine Demand Forecasting Using Trend Exponential Method at RSPG - Ajieb, Doni Fitrah; Sulistiowati, Sulistiowati; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Petrokimia Gresik Hospital is one of the major hospitals in Gresik. The problems faced by them is the demand for medicine are often not fulfilled. Based on these problems will require medicine demand forecasting application. Forecasting is very important in decision making. They require demand forecasting to ensure the booking amount of medicine. One method of forecasting is Trend Exponential. This method was chosen because it is based on existing data on companies that show a pattern trend. This method allows the demand forecast for the period ahead with. The expected outcomes of this app is it can predict the demand forecast for the period ahead, and also to help facilitate the process of forecasting demand for medicine